Natural Law, our Constitutions, and the Unborn - Graham, John (Revue générale de droit, 1996)
The problem of unenumerated constitutional rights in the United States and Canada is examined in order to seek a true and objective basis upon which judicial opinions may elaborate such privileges and immunities. The authentic root principles of fundamental law in both countries are traced to natural law as explained by Aquinas, Blackstone, Jefferson and other such legal philosophers. From this fund of knowledge, it is shown that natural law is a postulate of constitutional order in the United States and Canada, as illustrated by numerous judicial decisions which deal with freedom of contract based on the abolition of slavery, freedom to pursue useful knowledge, and such like.Natural law as a postulate of constitutional order is shown to presuppose not only the existence of God, but also to ordain the equal dignity and certain "absolute" or "unalienable" rights founded on the spiritual reality of human nature, in terms of which all constitutional rights should be interpreted and expounded, including our unenumerated rights of privacy in matters of sexuality.The author then reviews the main American and Canadian cases on the difficult problem of abortion, giving focus to similarities and contrasts along the way. It is shown that, given the spiritual essence of humanity ordained by natural law, the unborn enjoy a unique legal status as persons, which is evident in the traditions of both the common law and the civil law, and that, consequently, those judicial decisions announcing broad and sweeping constitutional rights to terminate pregnancy are, in the final analysis, indefensible.At stake, says the author, is more than a practical resolution of our contemporary political dispute over abortion, for the question goes to the very heart of our whole system of law and justice.Prospects of future constitutional development, including avenues of possible compromise, are discussed.